2018
DOI: 10.13005/bpj/1603
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bone Mineral Density with Biochemical Parameters and Prevalence of Osteopenia and Osteoporosis in South Indian Population

Abstract: Osteoporosis is identifying based on the bone mineral density (BMD). The bone mineral mass or BMD exposes the amount of minerals present in a particular region of bone tissue. BMD measurement by DEXA is consideredas gold standard, but it is very expensive. The people of developing countriesare not interested to check BMD until the occurrence offracture. Therefore present study focusing any association of routine biochemical markers with BMD in osteoporosis and also planning to identify disease distribution sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The prevalence in women was estimated to be 15%; 4.7% of premenopausal women and 10.3% of post-menopausal women were affected. 9.7% of men in this study were found to be predisposed (Modagan et al, 2018;Zou et al, 2020). The prevalence % was recorded maximum in female than male in the current study which is in line with the previous studies (Ormarsdottir et al, 1999;Cheraghi et al, 2018).…”
Section: Resultssupporting
confidence: 91%
“…The prevalence in women was estimated to be 15%; 4.7% of premenopausal women and 10.3% of post-menopausal women were affected. 9.7% of men in this study were found to be predisposed (Modagan et al, 2018;Zou et al, 2020). The prevalence % was recorded maximum in female than male in the current study which is in line with the previous studies (Ormarsdottir et al, 1999;Cheraghi et al, 2018).…”
Section: Resultssupporting
confidence: 91%
“…Studies in many different countries have demonstrated that with increased communication between the orthopaedist, patient and patient’s PCP, there is increased usage of pharmacotherapeutics, calcium and vitamin D supplementation, and BMD assessment with DXA scan [ 14 17 ]. There is also good evidence that the use of calcium, vitamin D and pharmaceutical interventions results in a decreased risk of fragility fractures [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence in women was reported to be 15%; 10.3% was related to post-menopausal women, and 4.7% to premenopausal women. In this study, the prevalence in men was reported to be 9.7% [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found to be 9.7%, and 15% for males and females, respectively. 23 Similarly, Marwaha, RK et al 2011 showed that the prevalence of osteoporosis in an Indian population aged at 50 years and above who inhabited Delhi was 35.1%. It was 24.6% and 42.5% for males and females, respectively.…”
Section: Discussionmentioning
confidence: 99%